2010
DOI: 10.4018/jte.2010100106
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Cyberbullying and Cyberstalking Experiences and Factors Related to Victimization of Students at a Public Liberal Arts College

Abstract: This article shows the results of a study of the cyberbullying and cyberstalking experiences of students at a public liberal arts college. A survey was administered online to sophomores, juniors, seniors, and graduate students at the college. The prevalence rates were 10% for cyberbullying and 9% for cyberstalking, shown in the sample of 471 respondents. Traditional college students under 25 years of age were experiencing and participating in cyberbullying at higher rates than older college students. Prior exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 12 publications
6
72
4
3
Order By: Relevance
“…The percentage of victims was larger than the aggressors, which is consistent with other authors (Raskauskas & Stoltz, 2007). Kraft and Wang (2010) conducted a study with college students from New Jersey, and discovered that 10% had already been victims of cyberbullying and cyberstalking. Students below 25 years of age experienced more cyberbullying than older students.…”
Section: Cyberbullying In Higher Educationsupporting
confidence: 74%
See 1 more Smart Citation
“…The percentage of victims was larger than the aggressors, which is consistent with other authors (Raskauskas & Stoltz, 2007). Kraft and Wang (2010) conducted a study with college students from New Jersey, and discovered that 10% had already been victims of cyberbullying and cyberstalking. Students below 25 years of age experienced more cyberbullying than older students.…”
Section: Cyberbullying In Higher Educationsupporting
confidence: 74%
“…Also because of the potential reasons for the high frequency of school violence that are possibly related to the sudden and drastic biological and social changes experienced by adolescents (Li, 2007). However, these phenomena are not only present in adolescence, they also occur during the university years with young adults (Akbulut & Eristi, 2011;Azevedo, 2013;Dilmaç, 2009;Finn, 2004;Francisco, 2012;Kraft & Wang, 2010;Souza, 2011;Walker, Sockman, & Koehn, 2011). Finn (2004) mentioned that what may lead to cyberbullying, is the easy access the university population has to the Internet and the wireless network in universities and faculties (in student residencies, libraries, etc.).…”
Section: Cyberbullying In Higher Educationmentioning
confidence: 99%
“…Stalking We utilized existing items that previous researchers have used to assess stalking in intimate relationships, including stalking in college relationships (i.e., Amar 2006;Basile et al 2006;Bjerregaard 2000;Chaulk and Jones 2011;Coleman 1997;Finn 2004;Jordan et al 2007;Kraft and Wang 2010;Menard and Pincus 2012;Tjaden and Thoennes 1998), as no agreed upon measure for stalking behaviors in college student dating relationships has been developed. In order to ensure appropriate measurement of a range of behaviors, we chose items that assessed stalking behaviors that occurred electronically (e.g., BYou sent pornographic images to your partner even though your partner did not want them^) and behaviors that do not occur electronically (e.g., BYou followed you partner without his/her knowledge^).…”
Section: Methodsmentioning
confidence: 99%
“…Our study used user-generated content and showed that structural message features (i.e., arousal level and virality) as well as behavioral outcomes (i.e., commenting) can play a role in motivating college students to take civic action against cyberbullying. Kraft and Wang (2010) maintained the majority of college students who are cyberbullied cope with cyberbullying alone, without any utility of community resources. First, college administrators as well as social media designers should attempt to offer resources for cyberbullying victims.…”
Section: Theoretical and Practical Considerationsmentioning
confidence: 99%